The toll for Charon's boat in the face of longevity risk: An examination of Basis risk in Longevity bonds. - Tsikkouris, Antonis (2007)
This paper will address the increasingly important topic of Longevity Risk. By providing an overview of the literature concerning the explanations behind the increasing human lifespan, as well as its implications on the public and private sectors, the paper outlines the solutions proposed to deal with Longevity Risk, where the focus shifts on the Capital Market Solution. Particular emphasis is given on Basis Risk and its effect on hedging instruments like Longevity Bonds. It is argued that the presence of Basis Risk is both inevitable and can prove financially significant for individual occupational pension schemes with varying scheme-specific risk profiles.